Analysis of Water Treatment by Moringa oleifera Bioflocculant Prepared Via Supercritical Fluid Extraction - Yusoff, Muhammad Azroie Mohamed; Lee, Choon Weng; Bong, Chui Wei (HARD Publishing, 2019)
In this study, we used supercritical fluid extraction to prepare Moringa oleifera as a bioflocculant and studied its efficacy in water treatment. Relative to the conventional solvent extraction method, supercritical fluid extraction produced 42% more bioflocculant and was a more efficient method with both time (about seven hours less) and cost savings (about USD30 less). The bioflocculant produced via supercritical fluid extraction was also smaller (18±5 µm) and more similar in size (Coefficient of Variation, CV = 28%) as opposed to conventional solvent extraction (23±8 µm, CV = 35%). It was able to reduce more than 95% of turbidity and up to 60% bacterial population. Its performance in reducing selected heavy metals from water samples was also generally better than aluminium sulfate or alum. Our study showed that with the exception of cost restrictions, M. oleifera bioflocculant produced via supercritical fluid extraction has the potential to replace alum in water treatment plants.